2020
DOI: 10.17816/ptors17538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brachial plexus block on the incidence of arterial hypotension and bradycardia events during shoulder arthroscopy in adolescents

Abstract: Background. The role and significance of the technical aspects of interscalene brachial plexus block in the occurrence of sudden arterial hypotension and bradycardia events during shoulder arthroscopy in a semi-sitting position are ambiguous. Aim. The study aimed to assess the effect of interscalene brachial plexus block on the incidence of hypotension-bradycardia events during shoulder arthroscopic surgery in adolescents in a semi-sitting position. Materials and methods. This retrospective analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Kantharaja et al investigated the adhesive adhesion of ductile TiN and brittle CrN thin-layers by analyzing acoustic emission signals from scratch tests under predetermined loads [ 12 ]. Trukhin et al used acoustic emission to detect damage to polymer thin-layers and found that the acoustic signal increased when corrosion occurred under the thin layer [ 13 ]. Rd A. et al related the size and propagation of defects in thin layers of plasma-sprayed zirconia at high temperatures to acoustic emission signal parameters [ 14 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Kantharaja et al investigated the adhesive adhesion of ductile TiN and brittle CrN thin-layers by analyzing acoustic emission signals from scratch tests under predetermined loads [ 12 ]. Trukhin et al used acoustic emission to detect damage to polymer thin-layers and found that the acoustic signal increased when corrosion occurred under the thin layer [ 13 ]. Rd A. et al related the size and propagation of defects in thin layers of plasma-sprayed zirconia at high temperatures to acoustic emission signal parameters [ 14 ].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Therefore, the high incidence and potential for catastrophic complications should be considered when shoulder intervention is performed in aged patients in the sitting position for long duration. [8][9][10] Neuropathy after RFA has been published as case reports following Third Occipital Nerve ablation with RFA. Mechanical injury to the nerve can be secondary to direct needle trauma, compression of the nerve, or stretching of the nerve during positioning.…”
Section: Discussionmentioning
confidence: 99%